The appearance of Lapland Buntings Calcarius lapponicus in song flight - Byrkjedal, Ingvar; Lislevand, Terje; Finset Fjeldheim, Vegard (Ornis Norvegica, 2016)
The territorial song flight of Lapland Bunting Calcarius lapponicus males has been described in the literature as similar to that of pipits Anthus spp. Observations at Hardangervidda, S. Norway, show that the buntings sing over their territories while gliding about more or less horizontally, quite different from the steep ascending and descending flight trajectories of singing pipits. Also, the buntings’ body plan during song flight differs strikingly from that of pipits, potentially creating a very different visual signal.